Implementation of Health Education Counseling on Breast Self Examination (BSE) with Android Media on Breast Cancer Prevention Behavior in Balikpapan - Hazanah, Sri; Nilam Noorma (Universitas Airlangga, 2023)
Background: Breast cancer is a frightening disease for women. The prevalence of breast cancer in Indonesia is 109 per 100,000 population. The most cancer in EastKalimantan in 2014 was breast cancer with 179 people and in 2015 it rose to 424 people, this case experienced an increase of 56.28%. Aims: The aim of the researchers was to implement breast self-examination health education counseling (BSE) with Android media on breast cancer prevention behavior in Balikpapan. Method: This research method is a quasi-experimental study with a one-group pre-test and post-test design. The sample in this study was 2 groups of cadres totaling 50 people, each 25 people in the control group and 25 in the intervention group with ages 18-55 years. Results: The results of the study showed an increase in knowledge (good 48%, enough 40%, less 12%) and increased behavior about BSE (good 44%, enough 48%, less 8%), there was a difference in knowledge before and after being given BSE counseling using android media (p-value = 0.362). There are differences in behavior before and after being given the BSE counseling treatment using Android media (p-value = 0.607). Conclusion: Providing counseling using Android media provides better benefits.